2017
DOI: 10.1016/j.amsu.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis: A 7 year retrospective cohort study of the epidemiology, aetiology and outcome from a tertiary hospital in Jamaica

Abstract: BackgroundAcute pancreatitis (AP) is a significant cause of acute abdominal pain, morbidity and hospitalisation. There was previously a dearth of studies exploring the incidence, risk factors and outcome of AP in the Caribbean region.Materials and methodsAll patients with a diagnosis of AP admitted to the University Hospital of the West Indies (UHWI) between 2006 and 2012 were reviewed. The epidemiological profile, risk factors, clinical presentation and outcomes of patients with AP were retrospectively studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
23
2
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 41 publications
12
23
2
3
Order By: Relevance
“…Similar results was obtained in the study done by Reid in Jamaica (71.8%). 3 Acute fluid collection was present in 33.715% of cases and this is in concordance with the results of Sameer et al in a study at bhopal where acute fluid collection was found in 34% of patients and Banday et al in a study conducted at Jammu where it was found to be 36%. 12,13 Respiratory system involvement was the most common systemic complication (16.5%).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similar results was obtained in the study done by Reid in Jamaica (71.8%). 3 Acute fluid collection was present in 33.715% of cases and this is in concordance with the results of Sameer et al in a study at bhopal where acute fluid collection was found in 34% of patients and Banday et al in a study conducted at Jammu where it was found to be 36%. 12,13 Respiratory system involvement was the most common systemic complication (16.5%).…”
Section: Discussionsupporting
confidence: 89%
“…Abdominal pain was present in all cases which were in concordance with the study done by Reid et al where abdominal pain was present in 96.7% cases. 3 Nausea and vomiting was present in 70.183% cases. Similar results was obtained in the study done by Reid in Jamaica (71.8%).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations